Association between psychological distress of each points of the treatment of esophageal cancer and stress coping strategy - Yu Ohkura; Kanako Ichikura; Junichi Shindoh; Masaki Ueno; Harushi Udagawa; Eisuke Matsushima (BMC Psychology, 2022)
Abstract Background Patients with esophageal cancer often feel depressed and are fearful of metastasis and death. Esophagectomy is an invasive procedure with a high incidence of complications. The objective of this study was to examine the association between psychological distress on each points of the treatment of esophageal cancer and stress coping strategy. Methods In total, 102 of 152 consecutive patients who attended the outpatient clinic at Toranomon Hospital between April 2017 and April 2019 met the eligibility criteria for inclusion in this study. Questionnaires designed to identify psychological distress and stress coping strategies were longitudinally administered at 5 time points from the time of the first outpatient consultation to 3 months after esophagectomy. Results Although ‘fighting spirit’ (OR 0.836, 95% CI 0.762–0.918; p < 0.001) and ‘anxious preoccupation’ (OR 1.482, 95% CI 1.256–1.748; p < 0.001) were strongly related to psychological distress before treatment, as time of treatment passes, ‘helpless/hopeless’ (OR 1.337, 95% CI 1.099–1.626; p = 0.004) was strongly related to psychological distress after esophagectomy. There were no relationships between psychological distress and individual patient characteristics, with the exception of ‘history of surgery’ and ‘final staging’. The concordance index was 0.864 at time 1, 0.826 at time 2, 0.839 at time 3, 0.830 at time 4, and 0.840 at time 5. Conclusions The relationship between psychological distress and the Coping strategies was stronger on each points of the treatment of esophageal cancer than that between psychological distress and individual patient characteristics. This study uses prospective basic clinical data and may provide the baseline information for risk stratification for psychological management and for future clinical studies in these patients.